Contrast-Enhanced Harmonic Endoscopic Ultrasonography of Solid Pancreatic Lesions - Kwek, Boon Eu Andrew (Medknow Publications & Media Pvt Ltd, 2013)
Endoscopic ultrasonography is the best modality for pancreatic lesion evaluation as its superior spatial resolution allows small lesions to be identified and fine needle aspiration (FNA) cytology performed under ultrasound-guidance. Despite this, differentiating benign from malignant lesions remains a challenge as conventional ultrasound imaging is unable to differentiate lesions accurately and tissue yield is poorly diagnostic or limited in patients with the chronic inflammation. Contrast-harmonic technology uses a wide-band transducer capable of inducing sufficient acoustic energy to create harmonic microbubble oscillations of the newer second-generation ultrasound contrast agents (UCAs). These microbubbles are more stable, remaining within the intravascular component longer and emit significantly more harmonic content than surrounding tissue, thus allowing pancreatic parenchymal differentiation and microvascular architecture visualization. The use of UCAs is generally safe, but should be especially avoided in patients with unstable ischemic heart disease. During CH endosonography, pancreatic adenocarcinoma is commonly seen as an inhomogenous hypoenhancing lesion, focal pancreatitis as a hypo- or iso-enhancing lesion and neuroendocrine tumor as a hyperenhancing lesion. The presence of hyperenhancement is a strong predictor of non-adenocarcinoma etiology. Furthermore, in patients with the chronic pancreatitis or biliary stents that may obscure pancreatic inspection, the addition of contrast-harmonic endosonography to guide FNA cytology improves its diagnostic yield and accuracy. Quantitative analysis of perfusion through the time intensity curve is promising as an objective and accurate method to differentiate pancreatic lesions. Furthermore, studies are required to fully determine the role of contrast harmonic endosonography in the differential diagnosis of solid pancreatic lesions.